2018
DOI: 10.1177/0004563218765570
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance evaluation of the standardization of assay values for serum total 25-hydroxyvitamin D concentration in Japan

Abstract: Background To assess the vitamin D nutritional status, serum total 25-hydroxyvitamin D (25(OH)D) concentration is measured. We used six automated 25(OH)D immunoassays (AIAs) available in Japan and certified by the Vitamin D Standardization Program (VDSP) at the U.S. Center for Disease Control and Prevention to assess the concordance of the assay results. Methods Serum total 25(OH)D concentrations in SRM 972a and 20 serum samples from patients were determined using three liquid chromatography-tandem mass spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Recent reports on studies similar to ours have demonstrated that current, commercially available immunoassays for 25(OH)D continue to lack standardization. One evaluated several LC-MS/MS and immunoassays in hospital and university laboratories in Japan [17]. Another was coordinated by the VDSP with samples distributed to 15 different laboratories.…”
Section: Brief Resumé Of the Resultsmentioning
confidence: 99%
“…Recent reports on studies similar to ours have demonstrated that current, commercially available immunoassays for 25(OH)D continue to lack standardization. One evaluated several LC-MS/MS and immunoassays in hospital and university laboratories in Japan [17]. Another was coordinated by the VDSP with samples distributed to 15 different laboratories.…”
Section: Brief Resumé Of the Resultsmentioning
confidence: 99%
“…Secondly, different regression techniques can be performed to conform to the assumption, and the equations are calculated to evaluate the results. It can be noticed that regression techniques are properly classified as they may be applied in two different situations identified as constant SD and constant CV in the EP document [15][16][17][18]. 95%CI of intercepts and slopes derived from the equations may be required to be below the total error allowable.…”
Section: Discussionmentioning
confidence: 99%